Peracetic acid for conditioning of municipal wastewater sludge Hygienization, odor control, and fertilizing properties - Luukkonen, Tero (Waste management (New York, N.Y.), 2020)
Copyright © 2019 The Authors. Published by Elsevier Ltd.. All rights reserved.